Long-term mortality rates of young stroke in Taiwan: A decade-long epidemiology population-based study. (December 2022) - Wu, Yu-ying; Chen, Po-Yuan; Wu, Cheng-Chun; Chen, Han-Jung; Liang, Cheng-Loong; Lee, Yi-Che; Lin, Chi-Wei; Hung, Chao-Ming; Lin, I-Fan; Wang, Hao-Kuang
Introduction: Stroke remains a leading cause of death worldwide. Stroke in young adults is an important issue, gaining extra attention in recent years. This study aims to investigate the mortality after stroke in young adults in Taiwan. Patients and methods: This is a registry- and population-based study in Taiwan of patients aged 20–50 years with first-ever stroke between 1999 and 2012, with follow-up until January 1, 2022. Patients and mortalities were identified through Taiwan National Health Insurance database. Results: The study population included 65, 097 patients with stroke (mean age, 42.6 ± 6.6 years; 30.5% woman). There were 23, 481 (36.1%) intracranial hemorrhage, 37, 522 (57.6%) ischemic stroke, and 4094 (6.3%) stroke not otherwise specified. At the end of follow-up, a total of 18, 248 deaths (28.0%) occurred during a median follow-up of 9.8 years (interquartile range, 6.4–13.7 years). Conclusion: Taiwan young adults who were 30-day survivors of first-ever stroke have significantly higher long-term mortality rates when compared to other population-based studies.